Exploring active citizenship through spoken word poetry - Phasha, Pheladi (Department of Drama, 2022)
This dissertation is concerned with developing the South African youth's active participation in formal politics. Spoken word poetry as an applied drama and theatre medium is of particular interest to this study and it argues that the art form can be used as a means of youth development in the area of formal politics. To illustrate its argument, the dissertation discusses how a programme of spoken word poetry was used to address the issue of youth formal political participation and developed a group of young people's enthusiasm to participate in formal national decision-making processes. The programme, titled Raising Participation, was conducted with the support of Africa Unite, a non-profit organisation in Cape Town that offered their school club members as participants in the programme. The workshops targeted young people who would be eligible to vote in South Africa's next general elections, set to take place in 2024. Chapter 2 discusses spoken word poetry as an applied drama and theatre medium and identifies the connections which make spoken word poetry an appropriate art form to use as an applied drama and theatre approach. Chapter 3 discusses the programme of activities, the theoretical framework that informed its design and the methods of data collection and analysis which were used. It also discusses Africa Unite and the partnership between the organisation and the programme. Chapter 4 discusses the findings of the programme and its successes and limitations, concluding the dissertation.